Perancangan dan Pembuatan Sistem Informasi Penilaian Pada SMK Siloam 2 Medan - Arief Rahman Hakim (Jurnal Multidisiplin Indonesia, 2025)
Siloam 2 Medan Vocational School is an institution that operates in the field of education and academics. Siloam 2 Medan Vocational School really needs an adequate system for managing and carrying out all school activities. One of them is the assessment information system at SMK Siloam 2 Medan which is currently not computerized and well integrated, so it still has many shortcomings in handling assessment problems. The approach used in research is the OOAD approach which uses several tools and work techniques, such as use case, activity diagram, sequence diagram, class diagram, component diagram, deployment diagram. And the development model used is the Waterfall model. Where the Waterfall model is a sequence of activities carried out in system development starting from requirements analysis, design, coding, implementation, testing, and maintenance. This model offers a way to create software in stages so that it is more organized. By implementing the design of the assessment information system at Siloam 2 Medan Vocational School which is web-based using PHP and HTML programming languages, the software chosen to design this application is Dreamweaver with XAMPP and mySQL database It is hoped that this will make it easier to manage all assessment data, without data errors or mistakes occurring in managing the data. So that the school or agency can achieve the goals that have been set optimally.